The Role of Music Aggregator Distribution Toward Music Performers in View of the Three Pillars of the Copyright System - Attamimi, Zeehan Fuad; Tajudin, Amalina Ahmad; Umar, Fadhil (Journal of Law and Legal Reform, 2024)
One of the works of art that is closely related to human life and economic value is music. The existence of music and songs include the scope of intellectual property copyright section. Copyright arises automatically to get protection and has economic value for its creator. Music actors, in this case the creator, can publish the results of their creativity more quickly to the general public through Music Aggregator. This becomes a commercial digital service provider in the form of a digital streaming plaform by distributing music that can be accessed anywhere and by anyone. This approach seeks to review the role of Music Aggregators in carrying out the distribution of music to the music performers in terms of the three pillars of the copyright system, namely by reviewing legislation number 28 of 2014 concerning copyright. In this case, as government support in making regulations that guarantee the rights of creators and legal protection of the works produced, it has been fulfilled but not fully because there is no specifically regulated copyright protection on digital platforms (Regulation). Infringement of musical copyright works on digital streaming platforms needs to be addressed through effective and efficient law enforcement, employing both litigation and non-litigation processes (Law Enforcement). The National Collective Management Institute, authorized to oversee the commercialized management of musical copyright works by Music Aggregators, play an important role in optimizing the function of royalty management. This involves facilitating the relationship between Music Actors as copyright holders and Music Aggregators as copyright users (Management).